Tinjauan Sistematis Literatur Tentang Efektivitas Kebijakan Kependudukan dalam Mendukung Pencapaian Program Keluarga Berencana Di Indonesia - Emi Handrina (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The transformation of population policy in Indonesia plays a crucial role in the success of the Family Planning (FP) Program in controlling population growth and improving the quality of life of the community. This article presents a systematic review of the literature (SLR) to evaluate the effectiveness of population policies in supporting the implementation of the FP program. The literature selection process followed PRISMA guidelines, focusing on publications relevant to population policy and FP program implementation in Indonesia between 2020 and 2026. The review results indicate that population policies have been adjusted to increase community participation, expand the distribution of FP services, and strengthen inter-agency coordination. Effective strategies include community-based approaches, integration of FP programs with primary health care, and the use of information technology for monitoring and evaluation. However, significant challenges remain, including disparities in access to services in remote areas, low reproductive health literacy, and socio-cultural differences that influence family participation. These findings emphasize the need for further research on the long-term evaluation of population policies and their impact on the sustainability of FP programs, while also providing a basis for formulating more adaptive, inclusive, and evidence-based population strategies.